Case Report: Multimodal Imaging Features of Pedunculated Liver Masses in Seven Dogs - Ko, Jaeeun; Hwang, Jeongyeon; Yoon, Hakyoung; Eom, Kidong; Kim, Jaehwan (Frontiers in Veterinary Science, 2020)
This study describes the multimodal imaging characteristics of pedunculated liver masses in seven dogs (Cocker Spaniel [n=2], Maltese [n=1], Shih-Tzu [n=2], Schnauzer [n=2]). These masses are anatomic variants of hepatic masses in which the center of the mass lies outside the liver contour. Prior to referral, only one dog had been diagnosed with a hepatic mass, four had been diagnosed with mid-abdominal masses of unknown origin, and two had been misdiagnosed with splenic head and pancreatic masses. Using radiographs, mass locations were classified as cranioventral (n=3), mid-abdominal (n=2), or craniodorsal (n=2). The gastric axis was deviated in various directions in four cases. Based on computed tomography (CT) findings, the masses were noted to originate from every liver lobe (two from the left lateral lobe) and to possess parenchymal (n=6) or vascular (n=1) pedicles. Histopathological results showed that three masses were benign (hepatic adenoma [n=1], nodular hyperplasia [n=2]) and four were malignant (hepatocellular carcinoma [n=3], cholangiocarcinoma [n=1]). For three dogs, arterial phase triple-phase CT maximum intensity projection images in the arterial phase clearly showed that the masses were connected to the hepatic artery. We propose that a pedunculated liver mass should be considered as a differential diagnosis when a mass is located in the mid-abdomen, even if it is separated from the liver and with the gastric axis deviated in various directions. We consider CT imaging to be a useful tool for diagnosis, evaluation, and surgical planning in dogs with a pedunculated liver mass.